EHL visco-plastic friction model in CVT shifting behaviour. (20th February 2004) - Carbone, G.; Mangialardi, L.; Mantriota, G.
This paper deals with the shifting dynamics of Van Doorne type metal V-belt CVT transmissions. A one-dimensional continuous model of the belt and a visco-plastic friction model (based on the results of the EHL lubrication theory) are proposed to describe the system behaviour under transient conditions. The model is able to correctly estimate the variator dynamics in "creep mode" (slow shifting manoeuvres) and in "slip mode" (rapid shifting manoeuvres) and to evaluate the borderline between these two operative conditions. The influence on the shifting speed of the ratio between the clamping forces acting on the two axially moving half-pulleys is evaluated together with the effect of the torque load and that of the drive pulley angular velocity. Moreover, a simple relation is obtained which links the shifting speed with the clamping forces ratio, the drive pulley rotating velocity, the torque load and the actual value of the speed ratio.